Effect of Ficus deltoidea leaves on glucose and glycogen metabolism in liver of normal and streptozotocin-induced diabetic rats / Nurdiana Samsulrizal - Samsulrizal, Nurdiana (2008)
Ficus deltoidea from the Moraceae family is commonly called "mas cotek" by the Malays. The Malay folklor e medicines believed that consuming a decoction of the vascular bundle of Ficus deltoidea led to a lowering of the blood glucose level of diabetic patients. The present study was designed primarily to evaluate the antidiabetic activity of Ficus deltoidea leaves on in-vivo and in-vitro models. Phytochemical examination of the plant by using simple qualitative screening methods showed that the aqueous and ethanolic extracts of Ficus deltoidea leaves contained saponins, flavonoids and tannins. The extracts also showed high inhibitory activity on a-glucosidase. To evaluate the effects of Ficus deltoidea leaves extracts on the hepatic activities of key glucose metabolic enzymes, non-diabetic and streptozotocin (STZ)-induced diabetic rats were treated with the extracts (200 mg/kg) for 2 weeks. Diabetes was induced in 1 month old rats by single intravenous injection of STZ at a dose of 65 mg/kg body weight. After a week, they were checked for fasting blood glucose concentrations to confirm the status of diabetes. The blood glucose concentrations were measured for 2 weeks upon the administration of Ficus deltoidea extract. A significant increase was observed in fasting blood glucose level in untreated diabetic rats. Diabetic rats also showed a significant decrease in the activities of hepatic hexokinase (HK), glucokinase (OK), phosphofructokinase (PFK), glucose-6-phosphate dehydrogenase (06PDH) and glycogen content. Conversely, a significant increase in the activity of fructose-1, 6bisphosphatase (FBPase) was observed in untreated diabetic rats. However , after 14 days treatment with the plant extracts, the activities of HK (p < 0.01) , GK (p< 0.05) , PFK (p < 0.05), G6PDH (p < 0.05) and the levels of hepatic glycogen (p < 0.05) were found to significantly increase while the activity of FBPase (p < 0.05) was significantly decreased at the end of the experiment. The findings suggest that Ficus deltoidea exert its antidiabetic effect by inhibiting ɑ-glucosidase, increasing glycolysis and decreasing gluconeogenesis.